Special Supplement: Health Literacy and Adult Basic Education - Maricel G. Santos; Michael K. Paasche-Orlow (SLACK Incorporated, 2019)
This supplement of HLRP: Health Literacy Research and Practice seeks to affirm the relevance of adult basic education (ABE) to advancements in the health literacy field. The worlds of health literacy and ABE have much in common, as both are preoccupied with promoting self-efficacy. Yet, they have largely remained unconnected in their research, policy, and practice. This supplement aims to highlight ways in which the health literacy and ABE fields have intersected and influenced each other to the benefit of adult populations with inadequate literacy skills, including those with limited print literacy and numeracy skills, and those with limited English proficiency.